Geological, geophysical, and geochemical constraints on the time-space evolution of Akan composite caldera, Hokkaido, Japan - Hasegawa, Takeshi; Nakagawa, Mitsuhiro; Kamiyama, Hiroyuki; Yamamoto, Akihiko (Frontiers in Earth Science, 2022)
Akan volcano has an elliptical polygon-shaped caldera (24×13 km) implying a complex mechanism of caldera formation. The Akan caldera was formed as a result of successive explosive eruptions from 1.4 to 0.1 Ma. On the basis of duration of dormancy and petrological features of juvenile materials, these eruptions can be grouped into 17 eruptive groups (Ak1-Ak17), each of which consists of a single or a sequential phase of eruptions. In order to investigate the processes of caldera formation, we focus on the younger eruptive groups (Ak1 to Ak7: 0.8 to 0.1 Ma), because have relatively large magnitude (> 10 km3) and likely to control the present caldera shape. We performed component analysis of lithic fragments from pyroclastic fallout deposits, gravitational survey of the caldera and petrological analysis of juveniles. We grouped Ak1-Ak7 into three types: type A (Ak1, Ak2), type B (Ak3 to Ak5) and type C (Ak6, Ak7) based on the lithic componentry, most of which are accessary and accidental fragments from vent and conduit areas. The characteristic lithic component in each type is: altered rock in type A, aphyric dacite in type B, and pyroxene andesite in type C. These data suggest that explosive eruption of each type derived from distinct sources. The bulk composition of juvenile materials of each type also shows distinct trends on Harker diagrams. These three chemical trends are nearly parallel, suggesting that three different magma systems were active. This is consistent with the lithic componentry showing three spatially distinct vent sources. The geological and petrological evidence is supported by a Bouguer anomaly map. Akan caldera is characterized by three circular closed minima, indicative of three depressed segments that correspond to the source regions, each of which possibly discharged the three types of magma. Caldera-forming eruptions of Akan caldera occurred from at least three distinct sources with distinct magma systems. In conclusion, the Akan caldera is a composite caldera and that the elliptical polygon shape reflects the distribution of multiple source regions. The case study of Akan caldera shows a possible time-space evolutionary pathway for a caldera complex where several small calderas are nested.